The Correlation Between the Expression Levels of Serum miR-19b and SOCS-1 mRNA and Clinical Symptoms in Patients with Allergic Rhinitis - Kang Z; Di L; Liu Y; Qu W; Zeng Y; Lu X; Wang L (Journal of Asthma and Allergy)
Zhaopeng Kang,1,* Lingling Di,2,* Yi Liu,3 Wei Qu,3 Yi Zeng,3 Xue Lu,3 Lixin Wang3 1Department of Andrology, Renmin Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China; 2Department of Otolaryngology Head and Neck Surgery, General Hospital of Ningxia Medical University, Yinchuan, Ningxia Hui Autonomous Region, 756099, People’s Republic of China; 3Department of Otolaryngology Head and Neck Surgery, Renmin Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lixin Wang, Department of Otolaryngology Head and Neck Surgery, Renmin Hospital, Hubei University of Medicine, No. 39 Chaoyang Middle Road, Shiyan, Hubei, 442000, People’s Republic of China, Tel +86-719-8666352, Email 1043275363@qq.comObjective: To investigate the correlation between the expression levels of microRNA-19b (miR-19b) and suppressor of cytokine signaling 1 messenger RNA (SOCS-1 mRNA) in the serum of patients with allergic rhinitis (AR) and clinical symptoms.Methods: This prospective study included a total of 86 patients with allergic rhinitis who were admitted to the People’s Hospital Affiliated to Hubei University of Medicine from January 2022 to January 2023. Seventy healthy individuals were included in the control group. The case group was further divided into a mild group (n=45) and a moderate to severe group (n=41) according to the severity of AR. The expression levels of miR-19b and SOCS-1 mRNA in serum samples of the two groups were detected and compared using real-time fluorescence quantitative polymerase chain reaction (qRT-PCR) technique. The receiver operating characteristic (ROC) curve and the area under the curve (AUC) were utilized to evaluate the predictive value of miR-19b and SOCS-1 levels for the severity of AR.Results: The expression level of miR-19b in the serum of the case group was 1.52± 0.36, significantly higher than that of the control group (1.02± 0.24, P< 0.05). Logistic regression analysis indicated that low levels of serum miR-19b and SOCS-1 mRNA were independent risk factors for moderate to severe AR, with an odds ratio (OR) of 3.575 (95% CI: 1.572– 8.133, P< 0.001) for miR-19b and 3.725 (95% CI: 1.637– 8.473, P< 0.001) for SOCS-1 mRNA. ROC curve analysis demonstrated that the levels of serum miR-19b and SOCS-1 mRNA had high accuracy in predicting moderate to severe AR, with AUC values of 0.879 (95% CI: 0.791– 0.940) and 0.795 (95% CI: 0.694– 0.875), respectively. When combined for prediction, the efficacy was significantly higher than that of individual detection, with an AUC value of 0.923 (95% CI: 0.856– 0.967), Z=3.261, P< 0.01.Conclusion: The expression levels of serum miR-19b and SOCS-1 mRNA are closely related to the severity of clinical symptoms in patients with AR and may serve as new biomarkers for evaluating the condition of AR and guiding treatment.Keywords: allergic rhinitis, microRNA-19b, SOCS-1 mRNA, logistic regression